Speech Processing In Digital Signal Processing - Hashim, Nik Mohd Zarifie; Hassan Basri, Hassriaizam; Jaafar, Anuar; Abd Aziz, Mohamad Zoinol Abidin; Salleh, Azahari; Ja'afar, Abd Shukur (Asian Research Publishing Network (ARPN), 2014)
-